2004
DOI: 10.1016/j.pain.2004.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for neck pain in general practice

Abstract: Prognostic studies on neck pain are scarce and are typically restricted to short-term follow-up only. In this prospective cohort study, indicators of short- and long-term outcomes of neck pain were identified that can easily be measured in general practice. Patients between 18 and 70 years of age, suffering for at least 2 weeks from neck pain were recruited by 42 general practitioners (GPs). Perceived recovery, pain intensity and neck dysfunction after 7 and 52 weeks were considered as outcome measures. Indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
87
0
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(106 citation statements)
references
References 16 publications
8
87
0
6
Order By: Relevance
“…In the present study, the "initial pain intensity" factor was treated as a continuous variable in the regression analysis, and the findings revealed that the higher the initial pain intensity, the higher the risk of developing chronic nonspecific neck pain. The 37,38) . Bot et al (2005) reported that more intense pain at baseline significantly reduced the probability of recovery at 3 months in patients with neck and shoulder pain 37) .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the "initial pain intensity" factor was treated as a continuous variable in the regression analysis, and the findings revealed that the higher the initial pain intensity, the higher the risk of developing chronic nonspecific neck pain. The 37,38) . Bot et al (2005) reported that more intense pain at baseline significantly reduced the probability of recovery at 3 months in patients with neck and shoulder pain 37) .…”
Section: Discussionmentioning
confidence: 99%
“…Neck/shoulder disorders are common in Western society, causing major medical and socio-economic problems [11,13]. Approximately two out of three individuals will at some time during their lives experience at least one episode of pain in their neck or shoulders [22].…”
Section: Introductionmentioning
confidence: 99%
“…The prognosis for those suffering from neck/shoulder pain is relatively poor. Not more than about the half of the subjects with neck/ shoulder pain are pain-free after 1-5 years [2,4,6,13,14,19,21,23,32,34].…”
Section: Introductionmentioning
confidence: 99%
“…These groups were created as broad categories to describe common clinical presentations of patients with neck pain by the rehabilitation department at Intermountain Healthcare in 2002 to evaluate clinical outcomes. Studies support that the clinical presentation of neck pain with arm pain, 24,25 neck pain with headache, 26 and neck pain from whiplash 27 differ in their clinical course compared to patients with acute, subacute, or chronic nonspecific neck pain (NSNP). 28 This strategy has been implemented at Intermountain Healthcare since 2002, and there is a 94.5% adherence rate in collecting these clinical data by physical therapists.…”
Section: Clinical Presentationmentioning
confidence: 99%